Early Maladaptive Schemas Related to Unipolar and Bipolar Depression: Similarities and Differences - Nergis LAPSEKÝLÝ; Mehmet AK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective and methodology: Cognitive theory of depression has begun to examine the difference between bipolar and unipolar depression in the context of thinking features. Yet, little is known about the same and seperated points of bipolar and unipolar depression. The objective is evaluating relationship between cognitive schemas of bipolar and unipolar patients. Bipolar and unipolar depression patients and a control group were enrolled in the study. Beck Depression Inventory, Young Mania Scale and Young Schema Questionnaire were administered to the groups. Results: There was significant difference between unipolar and control groups in “Abandonment/instability”. In “mistrust/ abuse” significant difference was between unipolar and bipolar and between unipolar and control groups. ln “entitlement/ self-centeredness” difference was between unipolar and control groups. In all other schemas, difference was between unipolar and control and bipolar and control groups. In these schemas, control group had significantly lower scores than others. Unipolar and bipolar groups were similar. Conclusion: In patient groups, schemas like defectiveness, incompetence, failure, vulnerability to danger and undeveloped self were indicative of low self-perception. This case draws attention to distortions in self-perception. When the absence of difference between bipolar and controls in “mistrust/abuse” and “abandonment/instability” schemas is evaluated in terms of cognitive triad, it is suggested that Environmental perspective in this group of patients did not exhibit pessimistic features. The only significantly different schema between unipolar and bipolar groups was “mistrust/abuse”. This suggests that bipolar group didn’t have negative thoughts like unipolar patients about the perception of the enviroment. [JCBPR 2012; 1(3.000): 145-151]